The Future of Europe : towards a two-speed EU? - Piris, Jean-Claude (Cambridge University Press CambridgeGB, 2012)
Proposes to examine all possible options for the future of the European, viz, a revision of the treaties; a continuation on the current path or the possibility of a group of Member States, the composition of which would probably be based on that of the euro area, acting temporarily in closer cooperation in order to be able to progress, without changing the EU treaties.